CONSEQUENCES OF NEW APPROACH IN PRODUCTION SYSTEM OF LOCAL KURDISH SLOW-GROWING BROILERS - & AL-Sardary, Mustafa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimed to investigate the effect of new production system of local Kurdish slow-growing broilers with special emphasis on organic technique. A total of 360 one-day-old chicks  mixed local slow-growing broiler genotype were distributed randomly into six treatments: (T1) control, feeding ad libitum commercial diet (indoor), (T2) feeding ad libitum  organic (indoor), (T3) feeding commercial % 75+ pasture, (T4) feeding organic % 75+  pasture, (T5) feeding commercial ad libitum  + pasture, and (T6) feeding organic ad libitum  + pasture. Each treatment consists of 60 birds with three replicates per treatment, 20 birds replicate. The results indicated that organic group treatment (T6) that fed ad libitum feed and pasture had the highest body weight and weight gain. Meanwhile it had the lowest feed intake and better FCR. Fatty acids contents between treatments found to have significant differences for both organic and commercial feed. Significant differences were found when compared treatments to each other. Raising slow-growing chickens under different system and feeding organic feed at a different level have had a potential effect on their performances and profile of fatty acids, and amino acids of their meat. It was concluded that feeding chicken organic feed ad libitum and allowing to access to the pasture performed better than all other treatment groups. Significant differences were found among treatments for sensory evaluation. Organic treatments and commercial treatments under same condition were not found any significant differences.